2012
DOI: 10.1007/s10067-012-1965-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the body image and level of pain, functional status, severity of depression, and quality of life in patients with fibromyalgia syndrome

Abstract: The aims were to investigate how the body image is affected in fibromyalgia syndrome (FMS) in comparison to healthy people, as well as to explore the relationship of the body image with the level of pain, functional status, severity of depression, and quality of life (QoL). Demographic variables, symptoms of fibromyalgia, and number of fibromyalgia tender points for 51 patients with FMS and 41 control subjects were recorded. All patients were asked to mark the level of pain on visual analogue scale (VAS). Six-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 17 publications
6
26
3
3
Order By: Relevance
“…They described changes in the perception of their body size and its relationship with space: they felt their body becoming larger and as though space was shrinking. These results are in line with those of Akkaya et al (2012) who report that body image is disrupted in fibromyalgia. Moreover, patients with fibromyalgia exhibit a higher frequency of falls and loss of balance despite an absence of inflammatory joint damage (Jones et al, 2009; Meireles et al, 2014), suggesting that a sensorimotor aspect of body awareness is also affected.…”
Section: Introductionsupporting
confidence: 93%
“…They described changes in the perception of their body size and its relationship with space: they felt their body becoming larger and as though space was shrinking. These results are in line with those of Akkaya et al (2012) who report that body image is disrupted in fibromyalgia. Moreover, patients with fibromyalgia exhibit a higher frequency of falls and loss of balance despite an absence of inflammatory joint damage (Jones et al, 2009; Meireles et al, 2014), suggesting that a sensorimotor aspect of body awareness is also affected.…”
Section: Introductionsupporting
confidence: 93%
“…In both studies, the associations between body-image dissatisfaction and QOL were not universal, and varied across different measures and subscales. These results differ from the findings of most previously conducted studies, in which full and consistent associations between these two variables were reported (Akkaya et al, 2012;Jelovsek & Barber, 2006;Steinmann et al, 2011). This difference could be explained by methodological factors, such as the small sample size or the selection of a less-sensitive QOL measure (SF-12 vs. SF-36).…”
Section: Discussion and Practical Implicationscontrasting
confidence: 85%
“…Among women with pelvic organ prolapse, worsening body image correlated with lower QOL, both physical and mental (Jelovsek & Barber, 2006). The same results were found among fibromyalgia patients (Akkaya, Akkaya, Atalay, Balci, & Sahin, 2012). Severity of body-image disturbance was also found to be associated with increased psychological distress among breast cancer survivors (Cohen, Mabjish, & Zidan, 2011;Przezdziecki et al, 2013), patients with pemphigus vulgaris (Mazzotti et al, 2011), and adult dialysis patients (Partridge & Robertson, 2011).…”
Section: Introductionsupporting
confidence: 54%
“…In a previously conducted study, worsening was shown in general body perception in patients with FM compared with patients without FM (47). In our study, the presence of FM in patients with FM also had a negative impact, especially on the personal evaluation of their own health.…”
Section: Discussionsupporting
confidence: 59%